IN-VITRO ANTIDIABETIC AND ANTIOXIDANT ACTIVITY OF CALAMUS ERECTUS ROXB. FRUIT: A WILD PLANT OF DARJEELING HIMALAYA - MITALI GHOSAL; PALASH MANDAL (International Journal of Pharma and Bio Sciences, 2013)
Calamus erectus Roxb. (CE) fruit under the family Arecaceae is traditionally used by the local people of Darjeeling Himalaya as an antidiabetic agent but no scientific reports are available yet. Hence this study was designed to determine the in vitro antioxidant and antidiabetic activities of two different parts viz. mesocarp and endocarp of Calamus erectus fruit. The extracts were screened for their possible in vitro antioxidant potentials by 2,2-diphenyl-1-picrylhydrazyl, reducing power, metal chelating, nitric oxide, superoxide, hydroxyl radical scavenging capacity and anti-lipid peroxidation assays and in vitro antidiabetic activity by α-glucosidase and α-amylase inhibition. The DPPH radical scavenging of methanolic extract of endocarp and mesocarp has IC50 values of 0.10 and 0.12 mg/ml fresh weight tissue respectively. All antioxidant assays of the extract were enhanced with the increasing amount of the concentration. The methanolic extract of different fruit parts (endocarp and mesocarp) showed concentration dependent α-glucosidase (IC50-1.69 and 2.00 mg/ml) and α-amylase (IC50-2.74 and 3.30 mg/ml) inhibitory activity. Hence α-glucosidase and α-amylase enzyme inhibition may be the possible mechanism for diabetic therapy and considered as a potential herbal drug for the management of type-II diabetes mellitus. The bioactivity of the plant extracts may be due to the presence of high total phenol content as determined through Pearson’s correlation and Principal Component Analysis. The in vitro studies clearly indicate that methanolic extract of endocarp of this fruit has more antioxidant and antidiabetic capability, also with extraordinary potential for their use in pharmaceuticals.